Enric Trillas: A Passion for Fuzzy Sets A Collection of Recent Works on Fuzzy Logic - Magdalena, Luis.; Verdegay, Jose Luis.; Esteva, Francesc; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents a comprehensive collection of the latest and most significant research advances and applications in the field of fuzzy logic. It covers fuzzy structures, rules, operations and mathematical formalisms, as well as important applications of fuzzy logic in a number of fields, like decision-making, environmental prediction and prevention, communication, controls and many others. Dedicated to Enric Trillas in recognition of his pioneering research in the field, the book also includes a foreword by Lotfi A. Zadeh and an outlook on the future of fuzzy logic.
Toward a Restriction-Centered Theory of Truth and Meaning -- A Note on Logical Connectives with Weak Duality -- Residual Implications from Discrete Uninorms. A Characterization -- A Classiffication Theorem for Continuous Quasi-Uninorms -- Globally Monotone Extended Aggregation Functions -- A Survey of Contributions To Fuzzy Logic and its Applications to Artificial Intelligence at the IIIA -- Gradual Structures of Oppositions -- Generation of Interval-Valued Fuzzy Negations from Trillas’ Theorem. The Case of Interval Type-2 Fuzzy Sets -- On Conjectures in T-Norm Based Fuzzy Logics -- Many-Valued Preorders I: The Basis of Many-Valued Mathematics -- Many-Valued Preorders II: The Symmetry Axiom and Probabilistic Geometry -- A Metasemantic Interpretation of Mamdani Systems -- Experimental Modeling for a Natural Landing of Fuzzy Sets in New Domains -- On Linguistic Variables and Sparse Representations -- Activating Generalized Fuzzy Implications from Galois Connections -- Randomness and Fuzziness: Combined Better than Unified -- Interpretability, a Silver Lining to a Fuzzy Cloud -- Prototype based Fuzzy Clustering Algorithms in High-Dimensional Feature Spaces -- Computing with Words for Decision Making versus Linguistic Decision Making: A Reflection on Both Scenarios -- Classification Validity Index -- On Fuzzy Modus Ponens to Assess Fuzzy Association Rules.-Applying Random Linear Oracles with Fuzzy Classifier Ensembles on WiFi Indoor Localization Problem -- Fuzzy Waves. Interference and Holography -- Fuzziness in CAR: Fuzzy Procedures for Robots and Cars -- Fuzzy Deformable Prototypes and Forest Fires Prediction and Prevention -- Hardware Implementation of Fuzzy Logic in Early Days of “Fuzzy” Era. Applying Random Linear Oracles with Fuzzy Classifier Ensembles on WiFi Indoor Localization Problem -- Fuzzy Waves. Interference and Holography -- Fuzziness in CAR: Fuzzy Procedures for Robots and Cars -- Fuzzy Deformable Prototypes and Forest Fires Prediction and Prevention -- Hardware Implementation of Fuzzy Logic in Early Days of “Fuzzy” Era. Generation of Interval-Valued Fuzzy Negations from Trillas’ Theorem. The Case of Interval Type-2 Fuzzy Sets -- On Conjectures in T-Norm Based Fuzzy Logics -- Many-Valued Preorders I: The Basis of Many-Valued Mathematics -- Many-Valued Preorders II: The Symmetry Axiom and Probabilistic Geometry -- A Metasemantic Interpretation of Mamdani Systems -- Experimental Modeling for a Natural Landing of Fuzzy Sets in New Domains -- On Linguistic Variables and Sparse Representations -- Activating Generalized Fuzzy Implications from Galois Connections -- Randomness and Fuzziness: Combined Better than Unified -- Interpretability, a Silver Lining to a Fuzzy Cloud -- Prototype based Fuzzy Clustering Algorithms in High-Dimensional Feature Spaces -- Computing with Words for Decision Making versus Linguistic Decision Making: A Reflection on Both Scenarios -- Classification Validity Index -- On Fuzzy Modus Ponens to Assess Fuzzy Association Rules.-Applying Random Linear Oracles with Fuzzy Classifier Ensembles on WiFi Indoor Localization Problem -- Fuzzy Waves. Interference and Holography -- Fuzziness in CAR: Fuzzy Procedures for Robots and Cars -- Fuzzy Deformable Prototypes and Forest Fires Prediction and Prevention -- Hardware Implementation of Fuzzy Logic in Early Days of “Fuzzy” Era.On Fuzzy Modus Ponens to Assess Fuzzy Association Rules.-Applying Random Linear Oracles with Fuzzy Classifier Ensembles on WiFi Indoor Localization Problem -- Fuzzy Waves. Interference and Holography -- Fuzziness in CAR: Fuzzy Procedures for Robots and Cars -- Fuzzy Deformable Prototypes and Forest Fires Prediction and Prevention -- Hardware Implementation of Fuzzy Logic in Early Days of “Fuzzy” Era.
Keywords: Computational intelligence; Applied mathematics; Engineering mathematics; Artificial intelligence; Control engineering; Robotics; Mechatronics; Computational Intelligence; Applications of Mathematics; Artificial Intelligence; Control, Robotics, Mechatronics